Hubungan Dukungan Suami Dengan Motivasi Ibu Dalam Memberikan ASI Eksklusif di Pekon Tegalsari Wilayah Kerja Puskesmas Gadingrejo Kabupaten Pringsewu Lampung - Yunitasari, Eva; Pringgayuda, Fitra; Agustanti, Dwi (Utan Kayu Publishing, 2021)
Many factors that influence some mother did not giving exclusive breastfeeding to her babies. The most influences factor is psychological factor. Support to the mother is the important point which is influence the mother to give exclusive breastfeeding. The result of exclusive breastfeeding for babies until six months itâ€™s about 22,28% and decrease until 46,69%. The purpose of this research is to perceive the correlation between husbandâ€™s supports with mother motivation for exclusive breastfeeding. This study included observational study with cross sectional study approach. The sample of the study consisted of 129 mothers with children under five years old. Mother motivation and husband support were collected by questionnaire that consists of 12 and 10 question for each other.Â The findings of the study revealed that 91 (70, 54) mothers have good support from her husband and 111 (86, 05%) mother have good motivation to give exclusive breastfeeding. Statistically, there was correlation between husband support with mother motivation for exclusive breastfeeding (p=0,039 with significances Î± = 0, 05). For the health services at Public Health Centre of Gadingrejo is to increase the quality of services for breast mother because health services have a role on breastfeeding successful. It can realize by giving information to the breast mother so they can be motivated to give exclusive breastfeeding.